Heroines of Jiangyong : Chinese Narrative Ballads in Women's Script - Idema, W. L. (Wilt L.) (Book collections on Project MUSE., 2009)
"Heroines of Jiangyong is the first English translation of a set of verse narratives recorded in the unique women's script (nushu) of rural Jiangyong County, Hunan, in southern China. This selection of Chinese folk literature provides a rare window into the everyday life of rural daughters, wives, and mothers, as they transmit valuable lessons about surviving in a patriarchal society that is often harsh and unforgiving. Featuring strong female protagonists, the ballads deal with moral issues, dangers women face outside the family home, and the difficulties of childbirth." "The women's script, which represents units of sound in the local Chinese dialect, was discovered by scholars in the late twentieth century, creating a stir in China and abroad." "This volume offers a full translation of all the longer ballads in women's script, providing an exceptional opportunity to observe which specific narratives appealed to rural women in traditional China. The translations are preceded by a brief introduction to women's script and its scholarship, and a discussion of each of the twelve selections."--Jacket